Cost-benefit based prioritisation of orangutan conservation actions in Indonesian Borneo. (October 2019) - Morgans, Courtney L.; Santika, Truly; Meijaard, Erik; Ancrenaz, Marc; Wilson, Kerrie A.
Abstract: Each year an estimated US$20–30 million is spent by government and non-government organisations in efforts to conserve the Bornean orangutan. However, recent population analysis reveals that these efforts have been unable to reduce species decline. A major aim of the Indonesian National Action Plan for orangutan conservation is to "improve in-situ conservation as the principal activity ensuring the orangutan's survival in its native habitats". This paper summarises and examines current investment in conservation activities and provides recommendations on the strategic allocation of funds for future conservation. The cost data of major conservation initiatives, including orangutan rescue and rehabilitation, habitat protection, habitat restoration and community education, was collated from non-government agency annual reports and primary literature. A recent population density and distribution model, and reports documenting the effectiveness of conservation strategies for the species were then used to calculate population trends in the presence and absence of interventions. Using an open-access cost-effectiveness resource allocator tool, we investigate expenditure and program performance. We then provide recommendations on how to strategically allocate conservation funding to future programs to ensure maximum effectiveness.